2019
DOI: 10.1016/s2468-2667(19)30155-0
|View full text |Cite
|
Sign up to set email alerts
|

Age at natural menopause and risk of incident cardiovascular disease: a pooled analysis of individual patient data

Abstract: Background Early menopause is linked to an increased risk of cardiovascular disease mortality; however, the association between early menopause and incidence and timing of cardiovascular disease is unclear. We aimed to assess the associations between age at natural menopause and incidence and timing of cardiovascular disease. MethodsWe harmonised and pooled individual-level data from 15 observational studies done across five countries and regions (Australia, Scandinavia, the USA, Japan, and the UK) between 194… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
250
4
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(268 citation statements)
references
References 60 publications
10
250
4
4
Order By: Relevance
“…Firstly, menopause age was the second most important determinant of vasomotor symptoms and their linkage was found to be negative in this study. Little study has been done on this topic and only a few independent suggestions have been made on a negative association between menopause age and cardiovascular disease [18] and a positive linkage between cardiovascular disease and vasomotor symptoms [19,20]. In a similar context, one would expect a negative relationship between menopause age and vasomotor symptoms, and this study supports this expectation given the high ranking of menopause age from the random forest in this study (2nd ).…”
Section: Discussionsupporting
confidence: 77%
“…Firstly, menopause age was the second most important determinant of vasomotor symptoms and their linkage was found to be negative in this study. Little study has been done on this topic and only a few independent suggestions have been made on a negative association between menopause age and cardiovascular disease [18] and a positive linkage between cardiovascular disease and vasomotor symptoms [19,20]. In a similar context, one would expect a negative relationship between menopause age and vasomotor symptoms, and this study supports this expectation given the high ranking of menopause age from the random forest in this study (2nd ).…”
Section: Discussionsupporting
confidence: 77%
“…Compared with women who had menopause at 50-51 years old, the risk of cardiovascular disease (coronary heart disease or stroke) was greater in women with POI (hazard ratio [HR] 1.55, 95% CI 1.38-1.73; p < 0.0001), with an almost linear dose-response relationship. Each year of decrease in age at menopause was associated with a 3% increased risk of cardiovascular disease 85 .…”
Section: Cardiometabolic Health In Women With Premature Ovarian Insufmentioning
confidence: 98%
“…In the largest study to date, data were pooled from 15 observational studies across five countries and regions from 301,438 women 85 . Compared with women who had menopause at 50-51 years old, the risk of cardiovascular disease (coronary heart disease or stroke) was greater in women with POI (hazard ratio [HR] 1.55, 95% CI 1.38-1.73; p < 0.0001), with an almost linear dose-response relationship.…”
Section: Cardiometabolic Health In Women With Premature Ovarian Insufmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous epidemiological studies have showed that women who experience premature menopause have a higher risk of overall mortality, cardiovascular diseases, neurological diseases, psychiatric diseases, osteoporosis, etc. [11][12][13][14][15][16]. The age of menopause was associated with reproductive, demographic, socio-economic, lifestyle and cultural factors [17,18].…”
Section: Introductionmentioning
confidence: 99%